Kemampuan Penalaran Matematis Siswa dalam Memecahkan Soal Cerita Ditinjau dari Gaya Belajar - Greskensia, NI Made Vemi; Sukayasa, Sukayasa; Pathuddin, Pathuddin; Mubarik, Mubarik (Jurnal Pendidikan Matematika : Judika Education, 2025)
This research aims to obtain students' mathematical reasoning abilities in solving sequence and arithmetic series word problems in terms of learning style. The method used is providing learning styles, written tests, interviews. The results of this research show that of the three visual, auditory and kinesthetic subjects the ones with the best mathematical reasoning abilities are the visual and kinesthetic learning style subjects. In conclusion, the mathematical reasoning ability of visual subjects is able to fulfill four indicators, namely representing ideas, determining solution strategies, implementing solution strategies, realizing solutions and interesting conclusions. The auditory subject's mathematical reasoning ability is able to fulfill four indicators, namely representing ideas, determining a solution strategy, implementing a solution strategy, solving a solution and drawing conclusions, but in the process there are errors so that the results obtained are less precise. Meanwhile, the mathematical reasoning ability of kinesthetic subjects is able to fulfill 3 indicators, namely representing ideas, determining completion strategies and implementing completion strategies. It's just that when drawing conclusions, kinesthetic subjects are unable to write down their conclusions. Keywords: Learning Style, Story Problems, Mathematical Reasoning Ability